Child Welfare Schemes on Special Children With Reference To Chennai Corporation - S. Ravichandran, S. Ravichandran; R. Premalatha, R. Premalatha (Journal of Neonatal Surgery, 2025)
The study examines the effectiveness and reach of child welfare schemes targeted at children with special needs within the Chennai Corporation. Children with special needs require comprehensive support from various institutions to ensure their development, well-being, and inclusion in society. Governments worldwide have introduced numerous welfare programs to cater to the unique needs of these children, addressing areas such as education, healthcare, social inclusion, and skill development. In India, several schemes are implemented at both the central and state levels, aiming to improve the quality of life for children with special needs. However, the extent to which these schemes benefit the intended recipients within urban settings like Chennai is not fully understood. The primary objective of this research is to evaluate the impact of child welfare schemes on special children in Chennai, with a specific focus on the awareness, accessibility, and utilization of these programs by families and caregivers. The study employs a mixed-methods approach, combining quantitative data collection through surveys and qualitative insights gathered from interviews with caregivers, educators, healthcare providers, and government officials involved in the implementation of these schemes. By examining both the structural framework of the schemes and the actual experiences of beneficiaries, this research aims to uncover gaps between policy and practice. Preliminary findings indicate that while there are numerous welfare programs available, factors such as lack of awareness, bureaucratic hurdles, and inadequate infrastructure limit their efficacy. Furthermore, socio-economic disparities and cultural stigma surrounding disabilities often exacerbate challenges faced by special children and their families. This study underscores the importance of tailored support, increased awareness, and enhanced service delivery to optimize the benefits of welfare schemes for special children. Recommendations include policy adjustments to improve accessibility, community-based awareness initiatives, and enhanced monitoring mechanisms to ensure that welfare programs fulfil their intended objectives within the Chennai Corporation. This research contributes to a deeper understanding of child welfare initiatives and offers insights for policymakers, practitioners, and stakeholders working towards an inclusive society for children with special needs.